Defining and Systematic Analyses of Aggregation Indices to Evaluate Degree of Calcium Oxalate Crystal Aggregation - Chaiyarit, Sakdithep; Thongboonkerd, Visith (Frontiers in Chemistry, 2017)
Crystal aggregation is one of the most crucial steps in kidney stone pathogenesis. However, previous studies of crystal aggregation were rarely done and quantitative analysis of aggregation degree was handicapped by a lack of the standard measurement. We thus performed an in vitro assay to generate aggregation of calcium oxalate monohydrate (COM) crystals with various concentrations (25-800 µg/ml) in saturated aggregation buffer. The crystal aggregates were analyzed by microscopic examination, UV-visible spectrophotometry, and GraphPad Prism6 software to define a total of 12 aggregation indices (including number of aggregates, aggregated mass index, optical density, aggregation coefficient, span, number of aggregates at plateau time-point, aggregated area index, aggregated diameter index, aggregated symmetry index, time constant, half-life, and rate constant). The data showed linear correlation between crystal concentration and almost all of these indices, except only for rate constant. Among these, number of aggregates provided the greatest regression coefficient (r=0.997; p<0.001), whereas the equally second rank included aggregated mass index and optical density (r=0.993; p<0.001 and r=−0.993; p<0.001, respectively) and the equally forth were aggregation coefficient and span (r=0.991; p<0.001 for both). These five indices are thus recommended as the most appropriate indices for quantitative analysis of COM crystal aggregation in vitro.